From Parking Tickets to the Pandemic: Fixed Penalty Notices, Inequity and the Regulation of Everyday Behaviours - Murray, Kath (The British journal of criminology, 2024)
Since the 1960s, Fixed Penalty Notices (FPNs) have become a widely used sanction in the United Kingdom, used to deal with various low-level offences. More recently, the sanction came to prominence as the mechanism chosen to enforce the Coronavirus Health Regulations. This article critically examines the decision to employ FPNs in this context, and the implications in respect of inequality and inequity. We show that the decision was at odds with contemporaneous policing trends, and, drawing on new research evidence, argue that the Regulations stretched FPNs beyond their intended use, creating inequalities in enforcement and inequitable punishment effects. Our findings raise policy questions about the impact of the Health Regulations and what actions should be taken in the event of future pandemics.